Potential effects of climate change on the threatened Malagasy poison frogs: A multispecies approach - Albert Carné; David R. Vieites; Neftalí Sillero (Ecosphere)
Abstract Climate change is exposing ecosystems to novel conditions, and understanding its potential effects on species distributions is crucial. Those effects can significantly affect species with narrow environmental requirements inhabiting closed systems where dispersal is limited. Madagascar is a highly biodiverse island, boasting high levels of amphibian species richness and endemism. The impacts of climate change on Malagasy amphibians are scarcely addressed, with studies focusing on single species or localities. We assessed the potential impacts of climate change on the distributions of the endemic Malagasy poison frogs of the genus Mantella, one of the most threatened and best‐studied frog genera in Madagascar, which contains species of global interest for the pet trade. We quantified each species' marginality, specialization, and tolerance and modeled their realized niches using the Maximum Entropy algorithm. We projected the models into current and future climates, using five Global Circulation Models, three socioeconomic scenarios, three future periods, and three dispersal scenarios. Our results suggest that 30% of Mantella species may gain habitat suitability extent, while 60% are predicted to lose it, with two threatened species forecasted to lose all suitable habitats island wide by 2100. Furthermore, 80% of species are forecasted to lose habitat suitability in currently occupied pixels, with losses exceeding 90%. Range shifts tracking their optimal niche conditions are expected for nearly all species, but the receptor areas are not always suitable. The current distribution extent is a good predictor of both tolerance and marginality, and tolerance can predict the conservation status in the genus Mantella. We found a linear relationship with higher marginality and tolerance linked to greater potential losses. We discuss the reliability and severity of the forecasts, the caveats of niche projections, and challenges in planning conservation based on them.